ANALYSIS OF THE RELATIONSHIP OF THE INDONESIA CONSTRUCTION INDUSTRY AND THE EXPORTING INDUSTRY USING INPUT-OUTPUT ANALYSIS (1995-2018): THE DEMAND SIDE AND SUPPLY SIDE APPROACH - Supriyadi, Joko
Various studies have revealed that the construction industry in developing countries is highly dependent on imported raw material inputs and equipment (Saka and Olanipekun, 2020; Barra, 2021; Muchdie et al, 2018). Even though increased imports can have an adverse effect on the domestic economy (Sukirno, 2021). On the other hand, Indonesia is a country with a small open economy (Juhro, 2020; Ananda, 2020; Ramayandi, 2011; Adhi et al, 2018; Purwanto et al, 2018), which can only develop by good if exports grow (Bykau and Kholkov, 2017). Nothing has been disclosed between the construction industry and exports. Therefore, this research seeks to reveal the linkages between Indonesia construction industry and exporting industry using input-output analysis. The results of the study show that the construction industry actively plays a role in supplying the input needs of all industries to meet the demand for exports of exporting industries. Overall, the construction industry supplied US$ 71668.63 million from 1995 to 2018. The trend has increased from US$ 856.03 million in 1995 to US$ 3463.38 million in 2018. Based on its supply structure, the construction industry has strong linkages with the mining industry. Meanwhile, based on the classification of demand-side and supply-side linkages, it was found that the construction industry's push capability is driven more by changes in primary inputs than final demand. It is also estimated that imports of construction industry raw materials used for export purposes were valued at USD 111.28 million in 1995 and USD 450.23 million in 2018.